2019
DOI: 10.1109/access.2019.2932797
|View full text |Cite
|
Sign up to set email alerts
|

Group Emotion Recognition Based on Global and Local Features

Abstract: In order to improve the accuracy of group emotion recognition, a group emotion recognition model based on global scene feature and local face feature is constructed in this paper. When extracting global scene features, with the consideration of that the different size of the background objects may have different influences on the emotion recognition, the paper proposes a feature extraction algorithm for the global scene based on the fusion of multi-scale feature maps. With the consideration of the emotion prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The photographer analysis could be further enhanced, for example, by considering photographer intentions [10] and their photo quality [52], besides, object detection performance can be enhanced by considering information fusion approaches [6], as well as improving detection of smaller sized objects [4]. Here, we only considered person detection, while person segmentation [22], face detection with facial expression analysis [54], group-level emotion recognition [60], or age estimation [1] will open more interesting opportunities. Besides objectlevel analysis, scene recognition [63] will help to further characterize photographers.…”
Section: Discussionmentioning
confidence: 99%
“…The photographer analysis could be further enhanced, for example, by considering photographer intentions [10] and their photo quality [52], besides, object detection performance can be enhanced by considering information fusion approaches [6], as well as improving detection of smaller sized objects [4]. Here, we only considered person detection, while person segmentation [22], face detection with facial expression analysis [54], group-level emotion recognition [60], or age estimation [1] will open more interesting opportunities. Besides objectlevel analysis, scene recognition [63] will help to further characterize photographers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in [ 27 ], several CNNs with different depths were used, but in this case using the softmax angular loss (A-Softmax) to make the learned characteristics more discriminative. In [ 40 ], after detecting the faces, the neural networks VGG-16 and MobileNet-v1 were used to extract the characteristics of each face. Instead of training a neural network, in [ 21 ], EmoNet was proposed.…”
Section: Related Workmentioning
confidence: 99%
“…More sophisticated fusion methods can also be used, such as neural networks. The Long Short-Term Memory (LSTM) neural network was used in [ 35 , 36 , 40 ] to learn how individual emotions affect the group emotion. Residual networks, such as cascade attention networks, were used in [ 25 , 32 ], to determine the influence of each face in the detection of the emotion of the group.…”
Section: Related Workmentioning
confidence: 99%
“…Local feature fusion [25] is a classic computer vision concept, which has been widely used in biometrics identification [26]. The traditional method is to use single local feature to train neural network to realize biometric recognition.…”
Section: B Local Feature Fusionmentioning
confidence: 99%
“…Min et al [28] verified the effectiveness of the multi-feature fusion algorithm in enhancing the model performance in the details of the VR panoramic image more than the single-feature fusion algorithm. Yu et al [29] suggested an emotion recognition model algorithm focusing on long short-term memory (LSTM) with the fusion of different local facial features, which acquired a 24.38% higher accuracy compared with the typical method.…”
Section: B Local Feature Fusionmentioning
confidence: 99%